KINERJA PRODUKSI KEPITING BAKAU Scylla serrata CANGKANG LUNAK PADA METODE PEMOTONGAN CAPIT DAN KAKI JALAN, POPEY, DAN ALAMI - Eko Harianto (Universitas Batanghari Jambi, 2015)
Types of crab leading export market is the mangrove crab Scylla serrata soft shell. Soft shell mud crab is a crab mangrove swamp phase moult (moulting). The methods used in the process of cultivation a soft shell mud crab is cutting of claws and Foot Paths methods, popey, and natural. The purpose of this research to determine the level of the highest efficiency among these methods by analyzing the survival rate of survival, growth rate, the amount of time molting crabs, crab molting time, growth of biomass as well as cost analysis. The seeds used was 7.49±0.21 cm in length and 110.52 ± 2.70 g in weight. The results showed that the average of survival rate for all treatment are 88,89-92,59% (P>0,05). The highest growth rate was in the treatment of cutting claws foot paths at 2.92% (P<0,05). Moult in the fastest method of cutting claws foot paths with an average crab molting on the 14th day, whereas the highest molting time there at night which is at 22.00-24.00. Based on the three treatments showed that treatment not a significanttly different (P> 0.05), but significantly different with growth rate of daily weight (P <0.05). In general, the production of soft shell mangrove crab natural treatment is more efficient than cutting of claws and foot path treatment and popey, whether viewed from the cultivation parameters and economic parameters.Keywords: Soft shell mangrove crab, molting, cutting of claws and foot path, popey, natural.